Performing the Chinese Eye Exercises and Children’s Vision—What Can We Learn from Primary Schoolers in Rural Northwestern China? - Huang, Juerong; Chen, Qihui; Du, Kang; Guan, Hongyu (New Advances in Medicine and Medical Science Vol. 6, 2023)
The chapter presents new evidence of the impact of regularly performing the Chinese eye exercises (CEE) on Chinese students’ visual outcomes, based on a large-scale survey dataset on 9,842 fourth graders randomly chosen from 252 primary schools in rural Northwestern China. We used an instrumental-variable (IV) technique and a bivariate-probit model to assess the effects of routinely performing the CEE on students' visual acuity and the incidences of visual impairment and myopia. Bivariate-probit estimates and IV estimates both show that the CEE has a negative impact on students' visual acuity. When compared to pupils who did not routinely perform the CEE, those who did were 6.2 percentage points more likely to have impaired vision and 7.6 percentage points more likely to be myopic. Our results imply that the frequently observed incorrect performance of the CEE among Chinese students imposes non-trivial hazards to their visual health, under the presumption that the correct execution of the CEE would not impair students' vision.